Enhancement of the Implementation of the Philippine Coast Guard National Service Training Program – Civic Welfare Training Service - Cua Jr., Edward Ylanan (Future Science / FSH-PH Publications, 2025)
This study assessed the implementation status of the Philippine Coast Guard National Service Training Program – Civic Welfare Training Service (PCG NSTP-CWTS) with the aim of developing relevant enhancement recommendations. Employing a mixed-methods design, the research involved 300 students who have undergone PCG Oriented NSTP–CWTS, who provided quantitative data through survey, and key implementers and stakeholders who offered qualitative insights via survey and interview. While students generally perceived the program's implementation as